DUKUNGAN SUAMI TERHADAP PEMBERIAN ASI EKSKLUSIF PADA IBU YANG MEMILIKI BAYI USIA 6-24 BULAN DI KOTA DENPASAR TAHUN 2017 - Permata, Seshia Arma Dwi; Widarsa, I Ketut Tangking; Kurniasari, Ni Made Dian (ARCHIVE OF COMMUNITY HEALTH; Vol 5 No 1 (2018): Juni (2018)DO - 10.24843/ACH.2018.v05.i01.p04, 2020)
ABSTRACT Exclusive breastfeeding is the provision of breast milk only for a minimum of six months without any complementary food. Indonesian government has been promoting exclusive breastfeeding program since 1990 with the National Minimum Service Standards (SPM) of exclusive breastfeeding coverage of 80%. However, exclusive breastfeeding coverage in Indonesia is still below the target. Exclusive breastfeeding coverage in Denpasar in year 2016 dropped sharply to 46.1%. The purpose of this study was to analyze the husband's support for exclusive breastfeeding for mothers who have babies aged 6 to 24 months old in Denpasar. This research is a quantitative analytic study using a cross-sectional approach, which was conducted at the Integrated Health Posts (Posyandu) in the area of Public Health Center (Puskesmas) I West Denpasar and Puskesmas II North Denpasar. Survey questionnaire was conducted to 96 samples selected using multistage random sampling technique. The results showed that more than a half of respondents received good support from their husbands, in the forms of informational support (66.7%), assessment support (63.5%), instrumental support (62.5%), and emotional support (61, 5%). It was concluded that husband's support had an influence of 80.2% where there were two variables that had a positive effect on exclusive breastfeeding, namely informational support (OR: 124.15; 95% CI: 10.50 - 1467.23) and instrumental support (OR: 15.75; 95% CI: 2.40 - 103.31). Husband’s support was still lacking on the provision of equipment to express breast milk, guidance on how to express the breastmilk, and on how to give the milk to the baby. Health workers, especially midwives, should provide early education to husband in order to improve husband’s participation and support to breastfeeding mothers. Keywords : Husband support, exclusive breastfeeding, 6 to 24 months old babies